Chylothorax associated with lymphatic reflux in a thoracic duct tributary after lung cancer surgery. Issue 15 (21st June 2021) - Ishida, Hironori; Nakazawa, Ken; Yanagihara, Akitoshi; Umesaki, Tetsuya; Taguchi, Ryo; Yamada, Akiko; Nitanda, Hiroyuki; Sakaguchi, Hirozo
Abstract: Chyle leaks are attributed to damage to the thoracic duct itself or its tributaries during surgery. Chylothorax after lung cancer surgery can occur due to damaged thoracic duct tributaries; however, little is known of the mechanism involved. A 71‐year‐old female underwent a left upper lobectomy with hilar and mediastinal lymphadenectomy for a 1.8‐cm primary squamous cell carcinoma, and developed a chylothorax a day later. Catheter lymphangiography revealed high‐flow chyle leaks from a damaged thoracic duct tributary, known as a bronchomediastinal lymph trunk, due to a lymphatic reflex from the thoracic duct. Subsequently, catheter embolization of the tributary repaired the chylothorax. The potential for persistent chylothorax after lung cancer surgery and successful lymphatic intervention should be noted. Abstract : Chylothorax after lung cancer surgery can be associated with lymphatic reflux into the damaged tributary from the thoracic duct. Catheter lymphangiography proved useful in detecting the location and direction of flow of lymphatic leakages as well as that in subsequent embolization.